2016
DOI: 10.1016/j.cgh.2016.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Variations in Duodenal Villous Atrophy Consistent With Celiac Disease in the United States

Abstract: Background & Aims Celiac disease is a common disorder with a worldwide distribution, though the prevalence among different ethnicities varies. We aimed to measure the prevalence of duodenal villous atrophy among patients of different ethnicities throughout the United States (US). Methods We performed a cross-sectional study of all patients who had duodenal biopsies submitted to a national pathology laboratory between January 2, 2008 and April 30, 2015. The prevalence of villous atrophy was calculated for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…These findings are the first to be reported outside of the tropics and in a Western society 25. The clinical relevance of this also expands to the USA where results from a national pathology database have identified that among patients undergoing duodenal biopsies it is those from the Punjab region of India that constitute the ethnic group with the highest prevalence of villous atrophy 52. It remains to be determined whether such patients had SNVA given that the US National Health and Nutrition Examination survey has found positive coeliac serology to be rare among non-whites 1…”
Section: Discussionmentioning
confidence: 55%
“…These findings are the first to be reported outside of the tropics and in a Western society 25. The clinical relevance of this also expands to the USA where results from a national pathology database have identified that among patients undergoing duodenal biopsies it is those from the Punjab region of India that constitute the ethnic group with the highest prevalence of villous atrophy 52. It remains to be determined whether such patients had SNVA given that the US National Health and Nutrition Examination survey has found positive coeliac serology to be rare among non-whites 1…”
Section: Discussionmentioning
confidence: 55%
“…The prevalence of both IBS and CD vary, depending on ethnicity and geographical location (7,(70)(71)(72), likely reflecting differences in diet, genetics, and culture. This metaanalysis included studies from multiple countries, recruiting patients of different ethnic origins.…”
Section: Discussionmentioning
confidence: 99%
“…Although our knowledge of CD is rapidly increasing, the possible role of Helicobacter pylori (HP) infection in CD, needs further evaluation. HP infection could influence the inflammatory and immune responses in small intestine and may therefore lead to the development of gluten‐related enteropathy in genetically predisposed individuals . In epidemiological and histomorphological studies, HP is shown as major etiological factor in patients with peptic ulcer disease, primary gastric mucosa associated lymphoid tissue lymphoma and gastric cancer …”
Section: Introductionmentioning
confidence: 99%
“…HP infection could influence the inflammatory and immune responses in small intestine and may therefore lead to the development of gluten-related enteropathy in genetically predisposed individuals. [4][5][6] In epidemiological and histomorphological studies, HP is shown as major etiological factor in patients with peptic ulcer disease, primary gastric mucosa associated lymphoid tissue lymphoma and gastric cancer. 7,8 Epidemiological studies have not proved an association between severe gastritis and CD.…”
Section: Introductionmentioning
confidence: 99%